ALLOMETRIC RELATIONSHIP IN THE CLAM KATELYSIA OPIMA (GMELIN) - Kalyanasundaram, M; Kasinathan, R (Indian Journal of Fisheries, 2011)
Analysis of covariance revealed length-weight relationship of Katelysia opima to be significantly different in immature, male and female clams, and correlation coeflScient to be significant at 0.025 level. The relationship between parameters length (L), height (H), width (B), whole live weight (W), body wet weight (Wb), body dry weight <Wd) and shell weight (Ws) of immature, male and female clams were studied in all permutations, and the relativistic mechanism determining the various relationships is discussed.